Meningkatkan Unjuk Kerja Akses Data Pada Aplikasi Berbasis Web - Katon Wijaya; Gabriel Indra Widi Tamtama (STMIK Budi Darma, 2022)
Web programming has become even more efficient when there are now jQuery plug-ins available. However, when the size of the database is very large, the performance of the web-based application decreases greatly. In a retail business, the search for available goods data is very necessary, if the data downloaded is limited in number there is a risk that the item sought will not be found. To improve the performance of web-based applications, a method will be made so that restrictions on the amount of data downloaded can be carried out but the search for the desired item data can still be found, so that the application program can display data with the search feature provided by the jQuery plug-in but can respond to user needs quickly. The method used in this research is a filtering technique by utilizing the multilevel Sequential Query Language (SQL) feature, so that the displayed data can be significantly reduced so that data access performance will increase. From this research, it is evident that with the multilevel filtering technique, the item data you are looking for can easily be found and can be displayed quickly using the jQuery Data Table plugin, so that programming becomes very efficient.